Interim Estimated Effectiveness of 2025-2026 COVID-19 Vaccines in Adults Using a Test-Negative Design - Ryan E. Wiegand; Sean Chickery; Duck-Hye Yang; Sarah W. Ball; Malini B. DeSilva; Kristin Dascomb; Stephanie A. Irving; Karthik Natarajan; Nicola P. Klein; Shaun J. Grannis; Toan C. Ong; Elizabeth A. K. Rowley; et al. (JAMA Network Open, 2026)
Importance The 2025-2026 COVID-19 vaccine, targeting JN.1 and JN.1-derived sublineages, became available in the US in September 2025. Objective To assess the estimated interim effectiveness of 2025-2026 COVID-19 vaccines against medically attended COVID-19 among immunocompetent adults aged 18 years or older in the US. Design, Setting, and Participants This case-control study used a test-negative design to investigate patient encounters captured in the Virtual SARS-CoV-2, Influenza, and Other Respiratory Viruses Network, an electronic medical record–based network of health care systems (253 emergency departments/urgent cares [ED/UCs] and 179 hospitals in 7 states) from September 3, 2025, to December 31, 2025. Patient encounters with COVID-19–like illness and a molecular or antigen SARS-CoV-2 test 10 days before to 3 days after the encounter date were included. Exposure 2025-2026 COVID-19 vaccination regardless of prior COVID-19 vaccination. Main Outcomes and Measures The main outcomes were COVID-19–associated ED/UC encounters and COVID-19–associated hospitalizations. Cases were defined as encounters with a positive molecular or antigen SARS-CoV-2 test and controls as encounters with a negative molecular SARS-CoV-2 test. The odds of 2025-2026 COVID-19 vaccination among cases and controls, adjusting for confounders, were compared and used to estimate vaccine effectiveness (VE) as (1 − adjusted odds ratio) × 100%. Results In 85 725 ED/UC encounters among adults aged 18 years and older (51 841 [60%] aged 18-64 years; 51 775 female [60%]), 206 of 3941 cases (5%) and 9453 of 81 784 controls (12%) received a 2025-2026 COVID-19 vaccination. Estimated VE against COVID-19–associated ED/UC encounters was 50% (95% CI, 42%-57%; median [IQR] time since 2025-2026 COVID-19 vaccine dose receipt, 47 [27-69] days). In 26 073 hospitalizations with a COVID-19–like illness (17 530 [67%] aged ≥65 years; 13 985 female [54%]), 60 of 1022 cases (6%) received a 2025-2026 COVID-19 vaccination compared with 3080 of 25 051 controls (12%). Estimated VE against COVID-19–associated hospitalization was 55% (95% CI, 41%-66%; median [IQR] time since 2025-2026 COVID-19 vaccine dose receipt, 46 [26-68] days). Among patients aged 65 years or older, estimated VE against ED/UC encounters was 48% (95% CI, 37%-56%; median [IQR] time since dose receipt, 48 [27-69] days; 33 884 encounters) and against hospitalization was 53% (95% CI, 37%-65%; median [IQR] time since dose receipt, 46 [26-69] days; 17 530 hospitalizations). Conclusions and Relevance In this study, receipt of 2025-2026 COVID-19 vaccination was associated with additional protection beyond existing immunity in adults against medically attended COVID-19, including ED/UC encounters and hospitalizations, compared with no receipt of a 2025-2026 vaccine dose. These findings suggest that adults can reduce their likelihood of severe COVID-19–associated outcomes by obtaining a 2025-2026 COVID-19 vaccination.